Some fixed-point theorems of convex orbital (α,β)-contraction mappings in geodesic spaces - Shukla, Rahul (Fixed point theory and algorithms for sciences and engineering, 2023)
The aim of this paper is to broaden the applicability of convex orbital ( α , β ) -contraction mappings to geodesic spaces. This class of mappings is a natural extension of iterated contraction mappings. The paper derives fixed-point theorems both with and without assuming continuity. Furthermore, the paper investigates monotone convex orbital ( α , β ) -contraction mappings and establishes a fixed-point theorem for this class of mappings.